Effectiveness of Implementation of the PT. Semen Padang Social Responsibility Program - Zikri Alhadi; Yulenri Arief Hidayat; Rahmadani Yusran; Nizamuddin Nizamuddin; Ory Riandini; Al Mukholis Siagiaan; Dally Angraini (Jurnal Public Policy, 2022)
This paper aims to describe the research results in the form of the effectiveness of the implementation of PT. Semen Padang in its Corporate Social Responsibility Program (CSR). Furthermore, the researcher describes the point of the performance of the CSR program PT. Semen Padang in Batu Gadang Urban Village. Moreover, this study aims to determine the implementation barriers the stakeholders faced and efforts to overcome the obstacles that hinder the effectiveness of the implementation of the CSR program of PT. Semen Padang. This study uses a qualitative approach with a descriptive method. Data was collected using observation, interviews, and documentation studies. In the findings of this study, it can be observed that the effectiveness of the implementation of the CSR program of PT. Semen Padang has an impact on the community empowerment process. This paper also explains that the data on potential beneficiaries of the program has not been consolidated; this has led to a double check by the Nagari Forum in identifying beneficiaries of the CSR program of PT. Semen Padang. Especially with the public’s understanding of the CSR program of PT. Semen Padang is still low, making the activities of this company become constrained in its implementation.